A Prospective Study on Fertility Preservation in Prepubertal and Adolescent Girls Undergoing Hematological Stem Cell Transplantation - Wikander, Ida; Lundberg, Frida E.; Nilsson, Hanna; Borgström, Birgit; Rodriguez-Wallberg, Kenny A. (Frontiers in Oncology, 2021)
Background: Hematological stem cell transplantation (HSCT) is an established method which has markedly increased the survival rate of hematologic malignancies since its introduction in the 1980’s. The conditioning for HSCT has known gonadotoxic effects and often leads to premature loss of fertility. In this study we have prospectively followed a cohort of girls undergoing HSCT and studied the outcomes of fertility preservation treatments performed before or after HSCT, as well as the long-term reproductive outcome. Methods: In this one-center prospective study, 40 girls counselled for fertility preservation prior to or after conditioning for HSCT for malignant or benign diseases at childhood or adolescence between 1990 and 2017 were included. The patients were presented the option to undergo cryopreservation of ovarian tissue or oocytes depending on their age and the time available. Follicle counts of the ovarian tissue and number of oocytes collected before or after HSCT were compared between patients treated for benign or malignant diseases. Hormone measurements post HSCT treatment were followed including FSH and AMH and reproductive outcomes and overall survival until January 2021 investigated. Results: In total, 35 girls and adolescents underwent fertility preservation before or after HSCT. Before HSCT, ovarian tissue was cryopreserved in 16 patients and two patients had oocytes preserved. Thirteen patients cryopreserved ovarian tissue after HSCT and eight patients returned to cryopreserve oocytes. Follicles were present in all tissue samples collected prior to HSCT, and in more than half of the samples collected post-HSCT. Half of the patients had spontaneous menarche or resumed menstruation post HSCT. Overall, 36 patients had survived at end of follow up and 7 patients had achieved parenthood. Conclusions: Since fertility loss is common following HSCT, fertility preservation should be offered to all patients. Fertility preservation treatments can be performed both before and after HSCT. Study Registration: ClinicalTrials.gov NTC04602962